H-Bridge based Five-Level Current-Source Inverter for Grid Connected Photovoltaic Power Conditioner - Suroso Suroso; Daru Tri Nugroho; Toshihiko Noguchi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
This paper presents an application of a new circuit configuration of H-bridge based five-level current-source inverter (CSI) used for grid connected photovoltaics system. In this topology, the intermediate level currents of the five-level current waveform are generated by connecting DC current module to the H-bridge CSI. Some new features can be derived using this new topology such as reducing the switching power device count, and reducing the inductor conduction losses of the inverter. The proposed five-level CSI is tested for grid connected photovoltaic system through computer simulation using PSIM software. Furthermore, the experimental test results of the proposed five-level CSI are presented. The results show that the inverter works properly generating a five-level current waveform and injecting a sinusoidal current into power grid with less harmonics distortion and with unity power factor operation.